[OP.4B.03] BI-DIRECTIONAL INTERACTION BETWEEN THE SYMPATHETIC NERVOUS SYSTEM AND SGLT-2 REGULATION. (September 2017) - Schlaich, M.; Rudnicka, C.; Herat, L.; Hricova, J.; Elliott, R.; Matthews, V.
Abstract : Objective: The sodium glucose co-transporter 2 (SGLT-2) mediates re-absorption of glucose from the renal proximal tubules. The SGLT-2 inhibitor empagliflozin has recently been associated with improved cardiovascular outcomes in patients with type 2 diabetes. We hypothesized that sympathetic nervous system (SNS) induced alterations of glucose metabolism may be mediated via regulation of SGLT-2 and investigated a possible interaction in cell culture and in a high-fat diet (HFD) mouse model. Design and method: We used the human renal proximal tubule cell line HK2 to assess changes in SGLT-2 expression in response to a range of concentrations of noradrenaline (NA), the main neurotransmitter of the SNS. Furthermore, we investigated the effect of SGLT-2 inhibition with dapagliflozin on SGLT-2 and tyrosine hydroxylase expression by immunohistochemistry in renal proximal tubules of C57BL6 mice fed either normal chow or a HFD for 10 weeks. Renal NA content was measured by a commercially available ELISA. Results: Bioactivity of NA was confirmed by detection of elevated phosphorylated ERK1/2 using Western Blotting. There were no cytotoxic effects of NA on HK2 cells as determined by a MTT assay at each time point. SGLT-2 expression in HK2 cells in response to treatment with NA was determined by immunocytochemistry at 24, 48 and 72 h post-treatment and a marked increase in SGLT-2 expression could be demonstrated. In the HFD mouse model, dapagliflozin treatment resulted in marked glucosuria and reduction in body weight, fasting glucose levels and mean arterial blood pressure. Compared to chow, there was a trend towards more pronounced SGLT-2 expression in proximal tubules of mice fed a HFD which was significantly up-regulated with dapagliflozin treatment. Most interestingly, dapagliflozin treatment resulted in a significant reduction in tyrosine hydroxylase expression in proximal tubules of HFD mice and a reduction in kidney NA content. Conclusions: SGLT-2 is up-regulated by NA both in vitro and in vivo. The observed reduction in both tubular tyrosine hydroxylase expression and kidney NA content with dapagliflozin treatment suggest a bi-directional interaction between the SNS and SGLT-2 regulation which may represent one of the mediators of improved cardiovascular outcomes reported for SGLT-2 inhibitors.